Is the revision of a primary TKA really as easy and safe as the revision of a primary UKA? - Staats, Kevin; Merle, Christian; Windhager, Reinhard; Waldstein, Wenzel (Annals of translational medicine, 2016)
Unicompartmental knee arthroplasty (UKA) and total knee arthroplasty (TKA) are surgical treatment options for unicompartmental knee osteoarthritis. Clinical results after both TKA and UKA are good, however, functional outcome and return to sport seem to favor UKA (1). UKA also is associated with a lower risk of perioperative complications, like venous thromboembolic events, stroke and myocardial infarction, and a lower blood transfusion rate (1).